2014
DOI: 10.4161/21624011.2014.945378
|View full text |Cite
|
Sign up to set email alerts
|

Anti-melanoma vaccines engineered to simultaneously modulate cytokine priming and silence PD-L1 characterized usingex vivomyeloid-derived suppressor cells as a readout of therapeutic efficacy

Abstract: Efficacious antitumor vaccines strongly stimulate cancer-specific effector T cells and counteract the activity of tumor-infiltrating immunosuppressive cells. We hypothesised that combining cytokine expression with silencing programmed cell death ligand 1 (PD-L1) could potentiate anticancer immune responses of lentivector vaccines. Thus, we engineered a collection of lentivectors that simultaneously co-expressed an antigen, a PD-L1-silencing shRNA, and various T cell-polarising cytokines, including interferon γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 55 publications
(126 reference statements)
3
49
0
Order By: Relevance
“…However instead of combining therapies, it would be more elegant if one drug could lead to activation of tumor-specific CTLs, while modulating MDSCs. Importantly, various studies have demonstrated that MDSCs can be reverted into stimulatory APCs under the influence of cytokines such as IL-12 [174], [175] or TLR ligands like CpG oligonucleotides [176], [177]. The latter has offered an opportunity to design a drug consisting of CpG oligonucleotides conjugated to STAT3 specific small interfering RNA (referred to as CpG-siSTAT3 conjugates) [178180].…”
Section: Targeting Signal Transducer and Activator Of Transcription 3mentioning
confidence: 99%
See 2 more Smart Citations
“…However instead of combining therapies, it would be more elegant if one drug could lead to activation of tumor-specific CTLs, while modulating MDSCs. Importantly, various studies have demonstrated that MDSCs can be reverted into stimulatory APCs under the influence of cytokines such as IL-12 [174], [175] or TLR ligands like CpG oligonucleotides [176], [177]. The latter has offered an opportunity to design a drug consisting of CpG oligonucleotides conjugated to STAT3 specific small interfering RNA (referred to as CpG-siSTAT3 conjugates) [178180].…”
Section: Targeting Signal Transducer and Activator Of Transcription 3mentioning
confidence: 99%
“…These range from the use of cell lines to the differentiation of bone marrow cells [77], [80], [100], [101], [181194]. In particular, ex vivo differentiation of bone marrow cells using conditioned media from GM-CSF secreting tumor cells has proven to be a successful approach [80], [175], [181], [184]. A proof-of-concept on the value of this strategy to obtain large amounts of MDSCs that resemble those found within various cancer types, including multiple myeloma, melanoma and colorectal cancer was delivered [80], [175], [181].…”
Section: In Vitro Generated Myeloid-derived Suppressor Cells: a Platfmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PDL1/PD1 blockade therapies are administrated systematically, such disruption must have a range of effects in the immunological synapse in peripheral tissues. When PDL1 is silenced in the peripheral tissues there is in fact an expansion of polyclonal CD8 T cells (43). Moreover, disruption of PDL1-PD1 interactions abrogates TCR down-modulation leading to the expansion of hyperactivated TCR high T cells.…”
Section: Functional Consequences Of Pdl1-pd1 Disruptionmentioning
confidence: 99%
“…For this reason, CD8 T cell infiltration can be used as a biomarker for therapeutic efficacy. Actually, tumor infiltration with PD1high and CTLA4high exhausted CD8+ T cells has been proposed as an accurate predictor of responses to anti-PD1 therapy in melanoma (43).…”
Section: Functional Consequences Of Pdl1-pd1 Disruptionmentioning
confidence: 99%